Controlling colours : function and meaning of colour in the British Iron Age - Hoecherl, Marlies (Archaeopress archaeology., 2015)
Colour defines our material world, operates as a communication tool and creates meaning. This book revisits well known and well documented sites or artefacts and explores their colours and colour connotations by looking at various contexts such as processes, landscape, iconography, body decoration or the colour connotations of death.